2013
DOI: 10.3892/ijo.2013.1998
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle mitochondrial uncoupling in a murine cancer cachexia model

Abstract: Approximately half of all cancer patients present with cachexia, a condition in which disease-associated metabolic changes lead to a severe loss of skeletal muscle mass. Working toward an integrated and mechanistic view of cancer cachexia, we investigated the hypothesis that cancer promotes mitochondrial uncoupling in skeletal muscle. We subjected mice to in vivo phosphorous-31 nuclear magnetic resonance (31P NMR) spectroscopy and subjected murine skeletal muscle samples to gas chromatography/mass spectrometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 102 publications
8
77
1
Order By: Relevance
“…Different research groups have shown that, in spite of the fact that the UCP2 gene is overexpressed in skeletal muscle from cachectic rats [14,15] and that muscle oxidative capacity -complex IV activity -is decreased, no alteration in either ATP synthesis or uncoupling are observed. These results are in contrast to the observation from our own research group where both ATP synthesis is decreased [16] and uncoupling is present [17] in mitochondria from tumour-bearing mice ( Figure 1). Other groups have found similar results demonstrating decreased ATP synthesis in skeletal muscle during cancer cachexia [18].…”
Section: Oxidative Damage and Mitochondrial Dysfunctioncontrasting
confidence: 86%
“…Different research groups have shown that, in spite of the fact that the UCP2 gene is overexpressed in skeletal muscle from cachectic rats [14,15] and that muscle oxidative capacity -complex IV activity -is decreased, no alteration in either ATP synthesis or uncoupling are observed. These results are in contrast to the observation from our own research group where both ATP synthesis is decreased [16] and uncoupling is present [17] in mitochondria from tumour-bearing mice ( Figure 1). Other groups have found similar results demonstrating decreased ATP synthesis in skeletal muscle during cancer cachexia [18].…”
Section: Oxidative Damage and Mitochondrial Dysfunctioncontrasting
confidence: 86%
“…In fact, Masaki et al have demonstrated that TNF regulates the in vivo expression of the UCP family differentially and tissue dependently [48]. A very recent data from our laboratory clearly indicate that uncoupling of oxidative phosphorylation is present in skeletal muscle of tumour-bearing animals [49]. Therefore, this phenomenon contributes, during the cachectic syndrome, to the generation of energetic inefficiency and, ultimately, to body weight loss.…”
Section: Oxidative Phosphorylation Uncoupling: Ucpsmentioning
confidence: 86%
“…However, the current lack of success for a single therapy indicates that cancer cachexia intervention may include different approaches, including non-pharmacological strategies, such as AET ( [32]; [5,90]). During cachexia progression, skeletal muscle endurance capacity is severely reduced [21,35,92,95]. The oxidative metabolism dysfunction, insulin resistance and increased glycolysis have been attributed to skeletal muscle mitochondrial dysfunction and the hypoxic environment of the tumor, mainly due to hypoxia-inducible transcription factors [33].…”
Section: Aet On Cancer Cachexiamentioning
confidence: 99%